POTATO MICROPROPAGATION IN A MEDIUM DEVOID OF ANY PLANT GROWTH REGULATORS - Buckseth, Tanuja (Potato Journal, 2023)
ABSTRACT: The MS media without any growth regulator is being used for the potato micropropagation. An analysis demonstrated that microplants developed without the growth regulators proved to have equivalent potential of increasing the multiplication rate of in vitro potato varieties. There was no significant difference in the growth and morphological parameters of potato cultivars regenerated with and without the use of growth regulators. The same cost effective protocol has been shared with the seed entrepreneurs and they are successfully following it in their labs.